2016
DOI: 10.1038/srep26509
|View full text |Cite
|
Sign up to set email alerts
|

SUMO5, a Novel Poly-SUMO Isoform, Regulates PML Nuclear Bodies

Abstract: Promyelocytic leukemia nuclear bodies (PML-NBs) are PML-based nuclear structures that regulate various cellular processes. SUMOylation, the process of covalently conjugating small ubiquitin-like modifiers (SUMOs), is required for both the formation and the disruption of PML-NBs. However, detailed mechanisms of how SUMOylation regulates these processes remain unknown. Here we report that SUMO5, a novel SUMO variant, mediates the growth and disruption of PML-NBs. PolySUMO5 conjugation of PML at lysine 160 facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
128
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 46 publications
(69 reference statements)
0
128
0
Order By: Relevance
“…SUMO1-3 are ubiquitously expressed while SUMO4 and SUMO5 are tissue-specific, and their functions are not completely defined yet (2,4). SUMO modifications can be distinguished in mono-, poly- and multi-SUMOylation (2,3) (Fig.…”
Section: The Process Of Sumoylationmentioning
confidence: 99%
“…SUMO1-3 are ubiquitously expressed while SUMO4 and SUMO5 are tissue-specific, and their functions are not completely defined yet (2,4). SUMO modifications can be distinguished in mono-, poly- and multi-SUMOylation (2,3) (Fig.…”
Section: The Process Of Sumoylationmentioning
confidence: 99%
“…All SUMOs use the same E1 and E2 enzymes in the process of SUMOylation, and can participate in forming polySUMO or mixed Ub-SUMO chains. SUMO4 seems to be a pseudogene or it is not processed89, while the recently reported SUMO5 shows tissue-specificity and participates in nuclear body formation10. In yeast and Drosophila there is a single SUMO homologue, Smt3.…”
mentioning
confidence: 98%
“…SUMO was first known to modify its canonical consensus sequence ψKxE/D (where ψ is an aliphatic residue and x any amino acid), however numerous studies reported other consensus sequences such as a phospho-dependent sequence, reverse consensus and non-consensus regions789. In human, three paralogs of SUMO are expressed ubiquitously (SUMO1, 2 and 3) in all cells, while SUMO4 is expressed in specific organs (kidney, lymph node and spleen), and SUMO5 was recently reported to be expressed in testes and blood cells10. Previous reports indicated that SUMO can interact with ubiquitin in a synergic or an antagonist manner1111213.…”
mentioning
confidence: 99%